Fishes in the Freshwaters of Florida - Robins, Robert H. (Robert Hale); Sheehy, Griffin E.; Randall, Zachary S.; Williams, James D. (James David), 1941-; Page, Lawrence M. (Book collections on Project MUSE., 2018)
This book is an essential identification guide to the 222 species of fishes in Florida's fresh waters. It includes recent discoveries, changes in taxonomy, marine species that enter Florida's fresh waters, and invasive species. Each species is presented with color photographs, key characteristics for identification, comparisons to similar species, habitat descriptions, and dot distribution maps. The authors have surveyed the extensive historical fish collections in ten natural history museums, providing a complete picture of the diversity and distributions of Florida's fishes. This guide includes some of the world's favorite sport fishes found in the state, including the Tarpon and Largemouth Bass. It also features three species native only to Florida--the Seminole Killifish, Flagfish, and Okaloosa Darter--and the smallest freshwater fish in North America, the Least Killifish. Ranging from the Panhandle to the Everglades, Florida's freshwater habitats include springs, creeks, rivers, lakes, ponds, swamps, marshes, and man-made canals. As Florida's human population grows, the state's freshwater environments are being changed in ways that threaten its native fishes. This book provides important information on the diversity, distribution, and environmental needs of native species and the threat posed by nonindigenous species, helping us monitor and protect Florida's water and its aquatic inhabitants.